Gas release of the dielectric coating of an anode and its effect on the characteristics of an ion diode with electron flux insulation by a radial magnetic field; Technical Physics Letters; Vol. 43, iss. 1 - Lopatin V. S. Valery Stepanovich; Stepanov A. V. Andrey Vladimirovich; Remnev G. E. Gennady Efimovich; Shamanin V. I. Vitaly Igorevich; Veresov A. E. Aleksandr Evgenjevich (2017, 2017)
Title screen